Impact of ionic liquids on the thermal properties of polymer composites - Shamsuri, Ahmad Adlie; Abdan, Khalina; Mohamed Yusoff, Mohd Zuhri; Jamil, Siti Nurul Ain Md. (Walter de Gruyter GmbH, 2024)
The integration of ionic liquids and polymer composites has become a promising way to improve their thermal properties, representing a notable advancement in the development of advanced materials for specific applications. Their thermal properties heavily influence the suitability of polymer composites for particular applications. It is imperative to understand and manipulate the thermal behavior of these composites to optimize their performance across various fields. In this mini-review, diverse polymer matrices and fillers utilized in polymer composites containing ionic liquids are categorized. Additionally, various ionic liquids employed in studies related to the thermal properties of polymer composites are identified. The impact of ionic liquids on the thermal properties of these composites is also briefly reviewed. The knowledge illustrated in this review enriches the understanding of the types of polymer matrices and fillers used in conjunction with ionic liquids, as well as their thermal properties. In a nutshell, imidazolium-based ionic liquids with tetrafluoroborate, bis(trifluoromethylsulfonyl)imide, hexafluorophosphate, halides, and hydrogen sulfate anions have the impact of improving the glass transition temperature, melting temperature, degradation temperature, and thermal conductivity of thermoplastic, thermosetting, and elastomer composites.